(untitled) (UNWE Yearbook, 2024)
The tourism industry, characterized by its complexity and interconnectedness, faces significant challenges such as economic downturns, natural disasters, and global pandemics, all of which underscore its vulnerability. Traditional risk management strategies have proven inadequate in addressing these multifaceted issues. This study explores the role of social entrepreneurship in enhancing tourism resilience through innovative and collaborative approaches. By fostering partnerships among local communities, stakeholders, and social entrepreneurs, social entrepreneurship drives sustainable development and creates resilient tourism destinations. Employing the two very diverse cases presented, this paper highlights the importance of adaptive strategies, collaborative networks, and social innovation in building a more sustainable and resilient tourism industry.